Do All Roads Lead to Rome? How Three Process Pathways Contribute to Transformative Innovation in Cross-Sector Partnerships - Margolis, Anna (Business & society, 2024)
Cross-sector partnerships (CSPs) offer much-needed collaborative spaces to address socio-ecological problems. Yet it is unclear if and how CSPs activities contribute to transformative innovation (TI) that addresses these problems and creates socio-ecological impact. Understanding how CSPs can contribute to TI is essential for CSP practitioners and researchers in order to address pressing socio-ecological problems. To better understand how CSPs can contribute to TI and socio-ecological impact, I conducted a multiple case-study of eight CSPs in the field of sustainable, circular packaging. The findings—based on the novel Transformative Innovation Process framework this article introduces—reveal three innovation pathways with different potentials for contributing to socio-ecological impact. Of the three, the complementary pioneering and adapting pathways have the greatest potential for contributing to socio-ecological impact, and the consolidating pathway has the least potential. This article makes theoretical contributions to the CSP literature as well as practical contributions for CSPs.